(untitled) (Journal of Hama University, 2020)
The aim of the research is to study the internal audit mechanism of Syria International Islamic Bank and to show its impact on its profitability, by showing the bank’s commitment to apply the internal control mechanism of internal audit, and to know the impact of internal audit on profitability represented in the rate of return on assets and rate of return on equity. In order to achieve the objectives of the research, the descriptive methodology was used and the primary data were collected for the research through the design of questionnaires and distributed to the studied sample to determine the extent of their application for internal audit, in addition to collecting and analyzing profitability data from the published financial statements for the period from 2008-2017, and testing the hypotheses related to the subject. Using spss statistical software. The research showed that the internal control mechanism represented by the internal audit (the Audit Committee, Internal Auditor) is applied by the bank in question, in addition to a moderate positive correlation between the internal audit mechanisms and the rate of return on equity, and a weak positive correlation between the internal audit mechanisms and the rate of return on assets. . A number of recommendations were proposed, the most important of which are the necessity of cooperation between the Audit Committee and the Shari’a Supervisory Board to take the necessary actions in relation to the Shariah matters.